2012
DOI: 10.1159/000345393
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume Is Increased in Infective Endocarditis and Decreases after Treatment

Abstract: Objectives: The aim of this study was to assess the mean platelet volume (MPV), an indicator of platelet activation in patients with infective endocarditis. Subjects and Methods: Twenty-nine patients with infective endocarditis and 29 healthy subjects were studied. Plasma MPV values in patients and control subjects were measured on admission and after 2 weeks of specific treatment of infective endocarditis. Results: The MPV was significantly higher among patients with infective endocarditis when compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
0
16
1
1
Order By: Relevance
“…As a difference from this result, previous studies demonstrated higher MPV in patients with IE who had no embolic event to this in control subjects [5,6]. We believe that if the authors had considered the above-mentioned confounding factors, they would perhaps have found different results.…”
contrasting
confidence: 83%
“…As a difference from this result, previous studies demonstrated higher MPV in patients with IE who had no embolic event to this in control subjects [5,6]. We believe that if the authors had considered the above-mentioned confounding factors, they would perhaps have found different results.…”
contrasting
confidence: 83%
“…In a study conducted by Becchi et al ., discharge MPV increased and PC decreased in patients who died from sepsis, but the opposite was true for patients who lived . Another study showed that MPV values were higher in patients with infective endocarditis, but these values decreased significantly after treatment .…”
Section: Discussionmentioning
confidence: 98%
“…The mean platelet volume (MPV) is a platelet index measured routinely as part of a complete blood count (CBC) in most clinical laboratories using automated analyzers [4][5][6][7]. In general, larger platelets are more active and thrombophilic than those of a normal or smaller size [4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The mean platelet volume (MPV) is a platelet index measured routinely as part of a complete blood count (CBC) in most clinical laboratories using automated analyzers [4][5][6][7]. In general, larger platelets are more active and thrombophilic than those of a normal or smaller size [4,7,8]. Consequently, MPV, a platelet size parameter, is used as a marker of platelet activation and function [8], and reflects platelet activation and production in bone marrow [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation